Penggunaan Komik Untuk Mengembangkan Keterampilan Menyampaikan Pendapat Siswa pada Pembelajaran Bahasa Indonesia - Harits, Dea Amelia (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2020)
Not all children in elementary schools can express opinions, some children are still reluctant to prefer passivity and silence when agreeing opinions. This causes because children are still experiencing difficulties in expressing what is in their thoughts and feelings, the child has not been able to ask for his opinion, as well as the media used by teachers in the learning process in class. Therefore, researchers are interested in using media to develop skills to express students' opinions. The results showed an increase in the average value on the assessment of the results of the pretest by 65.51, then the average value added increased at the posttest to 84. This was supported by the results of t-test calculations on the expertise supported by students and sig (0,000) < 0.05. The data shows that learning media is promising in developing the skills of conveying students' opinions.